Al-Aâ€™ZAMÄª DAN FENOMENA QIRAAT ALQURAN: ANTARA MULTIPLE READING DENGAN VARIANT READING - Yusuf, Khaeruddin (Hunafa: Jurnal Studia Islamika, 2014)
Absract: This article discusses one of the phenomena in the sciences of the Quran employing the point of view of Â the contemporary muslim scholar, Muá¸¥ammad Muá¹£á¹ÄfÄ al-Aâ€™zamÄ«. He asserted Â that one of the entrances used by the Orientalist to assault the authenticity of the Qur'an was through qiraat phenomenon. Al-Aâ€™zamÄ« critisized the Orientalistâ€™s views in terms of methodology, of analysis process and ofÂ  study results. The nonexistance of a dot and diacriticals did not become a problem for the text of the Koran since the system of the true recitation was taught by the prophet through memorization. The true system of reciting the Qurâ€™an had already existed Â in the minds of the Companions of the Prophet. The terms used in recitation cannot also be separated from Al-Aâ€™zamÄ«â€™s attention. He said Â that the term Â â€œmultipleâ€ (many) recitaions is more properly usedÂ  than the Â term â€œvariantâ€ (various) recitations.Kata Kunci: qiraat, multiple qiraat, tanda titik, diakritikal